The Roads to Congress 2022
XXIV, 371 p. 19 illus., 13 illus. in color.
Keywords: This book analyzes House and Senate campaigns in the 2022 midterm elections to reveal how distinctive campaign dynamics have a collective national impact. Despite serious efforts to overturn the results of the 2020 presidential race that went mostly unopposed by Republicans, the GOP appeared poised to gain seats, and perhaps control of Congress less than two years later. Their strong prospects reflected the familiar surge and decline of partisan electorates that political scientists have long used to explain midterm election outcomes. But despite a lingering global pandemic, the highest inflation in two generations, Wall Street facing its first bear market in more than a decade, the return of war among developed nations to the international stage, and largely successful efforts by a former President to maintain his grip on a party that lost the 2020 popular vote by 9 million, the story was clearly more complicated than the simple surge and decline thesis would suggest. Arriving on theheels of unprecedented challenges for democracy in America and surprising midterm election outcomes, The Roads to Congress 2022 provides an essential guide to understanding contemporary developments, with thematic chapters authored by more than thirty experts in campaigns and elections that explore the evolving state of party politics, electoral governance, redistricting, participation and representation, and profile the key races of the season. Sean D. Foreman is Professor of Political Science at Barry University, USA. Marcia L. Godwin is Professor of Public Administration at the University of La Verne, USA. Walter Clark Wilson is Professor of Political Science at the University of Texas at San Antonio, USA.